Fluorescence Behavioral Imaging (FBI) Tracks Identity in Heterogeneous Groups of Drosophila - Ramdya, Pavan; Schaffter, Thomas; Floreano, Dario; Benton, Richard (PLOS ONE, 2012)
Distinguishing subpopulations in group behavioral experiments can reveal the impact of differences in genetic, pharmacological and life-histories on social interactions and decision-making. Here we describe Fluorescence Behavioral Imaging (FBI), a toolkit that uses transgenic fluorescence to discriminate subpopulations, imaging hardware that simultaneously records behavior and fluorescence expression, and open-source software for automated, high-accuracy determination of genetic identity. Using FBI, we measure courtship partner choice in genetically mixed groups of Drosophila.